A data-driven model to quantify the impact of river discharge on tide-river dynamics in the Yangtze River estuary - Cai, Huayang (2023)
Understanding the role of river discharge on tide-river dynamics is of essential importance for sustainable water management (flood control, salt intrusion, and navigation) in estuarine environments. It is well known that river discharge impacts fundamental tide-river dynamics, especially in terms of subtidal (residual water levels) and tidal properties (amplitudes and phases for different tidal constituents). However, the quantification of the impact of river discharge on tide-river dynamics is challenging due to the complex interactions of barotropic tides with channel geometry, bottom friction, and river discharge. In this study, we propose a data-driven model to quantify the impact of river discharge on tide-river dynamics, using water level time series data collected through long-term observations along an estuary with substantial variations in river discharge. The proposed model has a physically-based structure representing the tide-river interaction, and can be used to predict water level using river discharge as the sole predictor. The satisfactory correspondence of the model outputs with measurements at six gauging stations along the Yangtze River estuary suggest that the proposed model can serve as a powerful instrument to quantify the impacts of river discharge on tide-river dynamics (including time-varying tidal properties and tidal distortion), and separate the contribution made by riverine and tidal forcing on water level. The proposed approach is very efficient and can be applied to other estuaries showing considerable impacts of river discharge on tide-river dynamics.